Are You Blue? Personality, Communication, and Leadership - Hillary Gleason (Academic Chairpersons Conference Proceedings, 2023)
This workshop will identify participants' dominant personality styles utilizing the True Colors questionnaire developed by Don Lowry in 1978. To that end, there will be a discussion on each color's communication and leadership strengths, weaknesses, and stressors. This is a fun activity that requires movement and most people enjoy. Finally, participants will be paired up with rotating partners and given a departmental chair scenario wherein they need to communicate and lead by utilizing what they have learned about dealing with the personality types of the colors. This exercise will help participants develop a strategic approach to their communication in order to ensure that their goals (to motivate, to collaborate, to direct, etc.) are achieved.
Keywords: Leadership; Communication; Personality; DEI; Psychology